OPTIMIZATION OF THE MODE OF DEPOSITION OF ASEPTIC CULTURES IN VITRO OF A RARE AND ENDEMIC SPECIES ALLIUM IVASCZENKOAE - Tagimanova, D.; Raizer, O.; Nagmetova , G.; Khapilina , O. (Eurasian Journal of Applied Biotechnology, 2024)
Optimization of the method of medium-term storage of the rare and endangered plant species Allium ivasczenkoae under in vitro conditions using modern approaches of biotechnology is an urgent task. Aseptic microplants Allium ivasczenkoae were used as starting material. The cultivation of microplants was carried out on nutrient media supplemented in various combinations with an increased concentration of sucrose, mannitol, chlorocholine chloride, ABA and BAP at various temperature and light conditions of deposition. The survival dynamics of A. ivasczenkoae varied depending on cultivation regimes. After 9 months of deposition, the survival of test-tube plants in mode 1 (control) was 20%, mode 2 - 60-80%, mode 3 - 30-50%. Under experimental conditions, the best results were obtained by depositing aseptic cultures for 9 months at a low positive temperature and low light intensity (mode 2) on nutrient media with the addition of CCC 120 mg/l and a sucrose concentration of 60 g/l and (B-1) and MS medium containing 0.5 mg/l BAP and 3 g/l mannitol (MSВМ). This mode of deposition made it possible to lengthen the period between transplants, as well as to maintain the viability of A. ivasczenkoae microplants from 60 to 80%. The data obtained make it possible to optimize the mode of medium-term storage of Allium ivasczenkoae under in vitro conditions for the mass production of rare species of bulbous plants in order to restore, reproduce and preserve the number of valuable gene pool and natural populations, create gene banks in vitro, reintroduce and green building.